Role Play Center Model Develops Early Childhood Language Skills: Model Pusat Peran Bermain Mengembangkan Keterampilan Bahasa pada Anak Usia Dini - Nadia alif Madinah; Choirun Nisak Aulina (Academia Open, 2025)
General Background: Early childhood represents a critical period for rapid development, particularly in language acquisition, which underpins communication, social interaction, and cognitive growth. Specific Background: Play-based learning approaches, especially structured role-play activities within learning centers, provide opportunities for children to practice verbal expression in meaningful contexts. Knowledge Gap: Despite widespread adoption of role-play centers in early childhood classrooms, limited qualitative evidence documents how their implementation supports language development and what contextual factors facilitate or hinder success. Aims: This study analyzes the implementation of a role-play center learning model in developing young children’s language abilities and identifies supporting and inhibiting factors in its application at TK Aisyiyah 38 Driyorejo. Results: Using a qualitative narrative approach with interviews, observations, and documentation, the findings indicate noticeable progress in vocabulary acquisition, speaking confidence, sentence formation, and social communication. Contributing conditions include a well-prepared learning environment, active teacher facilitation, parental involvement, and institutional support, while constraints involve limited materials, diverse child characteristics, and insufficient parental understanding. Novelty: The study offers an in-depth contextual description of daily role-play center practices and their relationship to expressive and receptive language use in authentic classroom interactions. Implications: These findings suggest that structured role-play environments, supported by collaborative school–family engagement and adequate resources, can serve as a practical pedagogical framework for fostering early language development in preschool settings. Highlights: Children demonstrated expanded vocabulary, clearer utterances, and greater willingness to communicate during thematic simulations. Successful implementation depended on environmental readiness, educator guidance, and family participation. Resource limitations and varied learner traits posed practical challenges to classroom application. Keywords:Role Play Center; Early Childhood Education; Language Development; Play-Based Learning; Qualitative Narrative